Instruments of Monetary Management : Issues and Country Experiences. (International Monetary Fund, 1997)
Many countries have reformed their monetary instruments over the last few years. Edited by Tomas J.T. Balino and Lorena M. Zamalloa, this volume deals with the design, implementation, and coordination of major monetary policy instruments, highlighting relevant country experiences. In particular, it discusses how to adapt those instruments to the financial environment as well as how to help this environment to develop.